1979
DOI: 10.1084/jem.149.5.1197
|View full text |Cite
|
Sign up to set email alerts
|

Active suppression of 1-fluoro-2,4-dinitrobenzene-immune T cells. Requirement of an auxiliary T cell induced by antigen.

Abstract: Shortly after the discovery of T-and B-cell interactions in humoral-immune responses, interest developed in the possible occurrence of interactions between T cells during cell-mediated-immune responses. T-T interactions occur in virtually all cellmediated-immune responses including graft-versus-host (GvH) 1 reactions (1), the development of cytotoxic T cells (2, 3), mixed lymphocyte reactions (4), responses to mitogens (5), generation of helper T cells (6, 7), and the development of delayed hypersensitivity (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1

Year Published

1980
1980
1993
1993

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 12 publications
7
58
1
Order By: Relevance
“…In contact sensitivity to DNFB, it was found that in order for DNP-specific suppressor T ceils to manifest their suppressive activities, the participation of another population of T cells termed auxiliary T cells (Ts-aux) is required. These T~-aux could be distinguished from TDn cells by their sensitivity to adult thymectomy and the presence of I-J region markers on the cell surface (38). It is possible that the interaction between T~ and T~-aux may be idiotype-specific whereas the expressed suppression is antigen specific, a notion similar in many respects to that discussed by Eardley et al (36).…”
Section: Antigen-and Receptor-driven Regulatory Mechanismssupporting
confidence: 51%
“…In contact sensitivity to DNFB, it was found that in order for DNP-specific suppressor T ceils to manifest their suppressive activities, the participation of another population of T cells termed auxiliary T cells (Ts-aux) is required. These T~-aux could be distinguished from TDn cells by their sensitivity to adult thymectomy and the presence of I-J region markers on the cell surface (38). It is possible that the interaction between T~ and T~-aux may be idiotype-specific whereas the expressed suppression is antigen specific, a notion similar in many respects to that discussed by Eardley et al (36).…”
Section: Antigen-and Receptor-driven Regulatory Mechanismssupporting
confidence: 51%
“…Several laboratories have demonstrated that. low dose Cy treatment is effective in removing elements of suppressor T cell circuits (9)(10)(11). It is likely, therefore, that suppressor T cells are responsible for preventing adoptive transfer of the isolated immune population into normal recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Rondinone et al (22) reported that CY-treatment of mice after sensitization with a higher dose of 1 x 108 SRBC enhanced the DTH response even though the response had been already aug mented by CY-pretreatment. They thought the most like ly target was the auxiliary cells to T suppressor cells of TDTH effector cells (26). The enhancement of 5 x 10' SRBC-DTH by FT-207 and 5-FU given after the sensitiza tion might occur through the same mechanism.…”
Section: Effect Of the Drugs On Meth A Tumor-neutralizing Activitymentioning
confidence: 99%